Kiat Ayah Membangun Pemahaman Tentang Kesetiaan Allah Pada Anak Di Keluarga Kristiani - Manurung, Kosma (Sekolah Tinggi Teologi Kanaan Nusantara, 2023)
The Bible shows that God is a faithful God. This can also be interpreted that when he makes a promise, Allah will be faithful in fulfilling every promise that He makes because loyalty is a character that is inherent in Him. Given the importance of God's faithfulness, fathers are encouraged to teach God's faithfulness to their children. An understanding of God's faithfulness needs to be built in a child because God is faithful and God's faithful nature wants from someone, this loyalty will also be related to the child's public life which contributes to future success. This article intends to describe father's tips in building an understanding of God's faithfulness to children in Christian families. By using narrative qualitative methods and literature studies, we strive to be able to provide in-depth, coherent, and accurate explanations regarding the biblical narrative about God's faithfulness, the importance of God's faithfulness being understood by children and father's tips in building an understanding of God's faithfulness to their children. In conclusion, a father will maximally build an understanding regarding God's faithfulness to his child if he provides this understanding from a young age, does it on an ongoing basis, teaches by setting a living example for his children, and becomes a friend who always supports his child.Alkitab menunjukan bahwa Allah adalah Allah yang setia. Ini juga bisa dimaknai bahwa ketika berjanji maka Allah akan setia menepapati setiap janji yang Dia ucapkan karena kesetiaan merupakan karakter yang sudah menyatu dalam diriNya. Mengingat pentingnya kesetiaan Allah, maka para ayah didorong untuk mengajarkan tentang kesetiaan Allah pada anaknya. Pemahaman mengenai kesetiaan Allah perlu dibangun pada diri seorang anak karena Allah adalah setia dan sifat setia Allah inginkan dari seseorang, kesetiaan ini nantinya juga terkait dengan kehidupan publik anak yang bersumbangsih pada kesuksesan masa depan. Artikel ini bermaksud menjabarkan kiat ayah dalam membangun pemahaman tentang kesetiaan Allah pada anak di keluarga Kristiani. Dengan menggunakan metode kualitatif naratif dan kajian litaratur diupayakan mampu memberikan penjelasan yang mendalam, runut, juga cermat perihal narasi Alkitab tentang kesetiaan Allah, pentingnya kesetiaan Allah dipahami oleh anak, serta kiat ayah dalam membangun pemahaman kesetiaan Allah pada anaknya. Disimpulkan, seorang ayah akan sangat maksimal membangun pemahaman terkait kesetiaan Allah pada anaknya jika memberikan pemahaman ini sedari kecil, dilakukan secara berkelanjutan, mengajari dengan menjadi contoh hidup bagi anak, serta menjadi sahabat yang selalu mendukungnya.